Implikasi Perkembangan Pariwisata Terhadap Sosial Ekonomi Masyarakat Di Desa Sibunga – Bunga, Kecamatan Sinembah Tanjung Muda (STM) Hulu, Kabupaten Deli Serdang, Sumatera Utara - Darma, Rio Sulistia; Pujani, Luh Putu Kerti (JURNAL DESTINASI PARIWISATA, 2018)
Tourism development will trigger positive or negative implication to the local communities. In term of socio-economic, Sibunga-bunga village is one of the village which has been affected by tourism development. It can be seen from the increasing number of local people who leave the agricultural sector and turn to the tourism sector . The aim of this research is to know the tourism development phase and socio-economic implication to the people of Sibunga-bunga village.                   The Data were collected through observational, interviews, and documentations, those data were described qualitatively. The tourism life cycle theory (TLCT) is proposed and tested in order to identify the tourism development phase. The socio-economic implications are presented with pictures to get a clear understanding of the facts and findings.                   The result of the study shows that the tourism development phase of sibunga-bunga village is on involvement. Tourism development of Sibunga-bunga village has positive implications to create job opportunities, to increase local’s income. Unfortunately, it was followed by negative impatcs such as in the form of violations of rules set by the managers of tourist attraction which may damage the surrounding environment, Keywords : Tourism development, implication, socio-economic, Sibunga-bunga village